Are COVID-19 Vaccine Preference and COVID-19 Risk Differ in Individuals Living with HIV from The Normal Population? - Ayaz, Çağlayan Merve; Baştuğ, Aliye (Acta Medica, 2022)
Objectives: Coronavirus disease 2019 (COVID-19) may have a severe course in high-risk patients and people living with Human immunodeficiency virus (HIV, PLWH)) are also in this risk group. The aim of the study was to compare the history of COVID-19, vaccination status, vaccine doses, and vaccine preferences of PLWH with the normal population. Materials and Methods: This study was a retrospective cross-sectional survey study. The PLWH were study group and patients without chronic disease were selected as a control group. Results: A total of 326 patients, 163 HIV positive and 163 without chronic disease, were included in the study. Of the patients, 142 (88.1%) were male, and the mean age was 46.69 ± 13.72 years. The number of patients who were not vaccinated was 36 (11.1%). When unvaccinated PLWH were evaluated, it was observed that women were less vaccinated than male patients (p=0.01). In PLWH, 145 (89.0%) of patients were vaccinated with single dose, 129 (79.1%) of patients with double dose, and 123 (75.5%) of patients with full dose; in the control group, 145 (89.0%) of patients with single dose, 131 (80.9%) of patients with double dose and 126 (77.3%) of patients with full dose were vaccinated. There was no difference between the groups in the preference of inactivated and mRNA vaccines (p=1.0). Before vaccination, 42 (12.9%) patients were infected. Twenty (12.3%) of these patients were in PLWH group, while 22 (13.5%) patients were in the control group. There were 28 (9.8%) patients who had COVID-19 during or after vaccination, and 10 (6.9%) of them were in PLWH group; 18 (12.4%) of them were in the control group. Conclusion: In our study, no difference was found in the vaccination status, vaccine preference, vaccination doses and COVID-19 history between two groups.